Servant Leadership and the Effect of the Interaction Between Humility, Action, and Hierarchical Power on Follower Engagement - Sousa, Milton (Journal of business ethics, 2017)
Servant leadership has been theorized as a model where the moral virtue of humility co-exists with action-driven behavior. This article provides an empirical study that tests how these two apparently paradoxical aspects of servant leadership interact in generating follower engagement, while considering the hierarchical power of the leader as a contingency variable. Through a three-way moderation model, a study was conducted based on a sample of 232 people working in a diverse range of companies. The first finding is that humble leaders showed the highest impact on follower engagement regardless of their hierarchical position. Less humble leaders in lower hierarchical positions seem to be able to compensate for that through a strong action-oriented leadership style. Most notably for leaders in high hierarchical positions, the moral virtue of humility seems to strengthen the impact of their action-oriented leadership the most. These findings provide empirical support and a better understanding of the interplay between the moral virtue of humility and the action-oriented behaviors of servant leadership.